Pengaruh employee engagement dan big five personality terhadap organizational citizenship behavior tenaga pengajar Fakultas Ekonomi Universitas Swasta di Surakarta - Suprayitno Suprayitno; Sutarno Sutarno (Journal of Business & Banking, 2021)
This study aims to determine the effect of the employee engagement and the big five personality on organizational citizenship behavior (OCB). The object of this research is the lecturers of the Faculty of Economics, Surakarta City Private University. The research used the quantitative method, with SPSS 23.0, for analyzing the data. The data obtained by  distributing a list of questions to 36 lecturers of the Faculty of Economics, Surakarta City Private University, using purposive sampling technique. The research instrument was tested using validity and reliability tests. Prior to the hypothesis test using the multiple linear regression analysis tool, the classical assumption test was carried out, while the t test used to determine the significance of the influence of the independent variables on the dependent variable. To find out whether the regression model can be used to predict the effect of the independent variable on the dependent variable or the model accuracy test, the F test is used. The results of the analysis in this study indicate that employee engagement has a significant effect on organizational citizenship behavior, while big five personality have positive but insignificant effect on the organizational citizenship behavior.